2019
DOI: 10.1101/gad.314633.118
|View full text |Cite
|
Sign up to set email alerts
|

BRN2 suppresses apoptosis, reprograms DNA damage repair, and is associated with a high somatic mutation burden in melanoma

Abstract: Whether cell types exposed to a high level of environmental insults possess cell type-specific prosurvival mechanisms or enhanced DNA damage repair capacity is not well understood. BRN2 is a tissue-restricted POU domain transcription factor implicated in neural development and several cancers. In melanoma, BRN2 plays a key role in promoting invasion and regulating proliferation. Here we found, surprisingly, that rather than interacting with transcription cofactors, BRN2 is instead associated with DNA damage re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 109 publications
4
32
2
Order By: Relevance
“…POU3F2, which belongs to the class III POU factors, also called Brn2 or N-Oct3, has been reported to be closely associated with cell proliferation or even elevated the potential for metastasis [22][23][24]. Brn2 was revealed to inhibit apoptosis and reprogram DNA damage repair, and was connected with a high somatic mutation burden in melanoma [36]. It has been observed that POU3F2 conduced to cellular responses against oxaliplatin in human colon cancer cells by regulating tNOX [37].…”
Section: Discussionmentioning
confidence: 99%
“…POU3F2, which belongs to the class III POU factors, also called Brn2 or N-Oct3, has been reported to be closely associated with cell proliferation or even elevated the potential for metastasis [22][23][24]. Brn2 was revealed to inhibit apoptosis and reprogram DNA damage repair, and was connected with a high somatic mutation burden in melanoma [36]. It has been observed that POU3F2 conduced to cellular responses against oxaliplatin in human colon cancer cells by regulating tNOX [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although BRN2 can bind elements within the MITF promoter, and can clearly suppress a proapoptotic gene expression program (Herbert et al 2019), it is also possible that it exerts its transcriptional function by cooperating with other sequence-specific transcription factors rather than regulating transcription by itself. Notably, mass spectrometry (MS) analysis of BRN2-associated proteins failed to identify a significant association with non-DNA-binding transcription cofactors.…”
Section: Repressors Of Mitf Mrna Expressionmentioning
confidence: 99%
“…Notably, mass spectrometry (MS) analysis of BRN2-associated proteins failed to identify a significant association with non-DNA-binding transcription cofactors. Instead, BRN2 is associated with the DNA-damage-response factors Ku70/Ku80 and PARP1 and plays a role in DNA damage repair by enhancing nonhomologous end-joining at the expense of homologous recombination (Herbert et al 2019). Thus, an ability of BRN2 to exchange cooperating DNAbinding cofactors under different conditions-for example, in vitro versus in vivo-might explain how it could switch from a repressor to an activator of MITF.…”
Section: Repressors Of Mitf Mrna Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanoma tumours with activating β-catenin mutations exhibit enhanced MiTF and Brn2 expression. Larue shows that Mitf-M affects proliferation, survival and transformation of melanocytes by interfering with cyclin-dependent kinase 2 and 4, p21 and BRN2 [11,12].…”
Section: Workhop On Tumour Biology and Immunitymentioning
confidence: 99%